2018
DOI: 10.1055/s-0038-1669934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potentilla Fulgens L. on Selected Enzyme Activities and Altered Tissue Morphology in Diabetic Mice

Abstract: Introduction The objective of the present study was to investigate the in vitro inhibitory effect of the Potentilla fulgens extract on amylase, α- and β-glucosidase, and lipase, as well as its effect on the ultrastructure of the liver, of the kidneys, and of the eye tissues in alloxan-induced diabetic mice. The present study was designed to get further insight regarding the action of P. fulgens from what has been previously known and reported about this plant. Materials and Methods Roots of P. fulg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Additionally, incipient CA development was evaluated by TEM analysis at the six-week mark, to reassure anterior segment examination findings. Similarly to our results, Majaw et al observed a more severe disorder of lens fibres in four-week diabetic mice, compared to healthy controls, upon TEM examination [37].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, incipient CA development was evaluated by TEM analysis at the six-week mark, to reassure anterior segment examination findings. Similarly to our results, Majaw et al observed a more severe disorder of lens fibres in four-week diabetic mice, compared to healthy controls, upon TEM examination [37].…”
Section: Discussionsupporting
confidence: 92%
“…Previously in different studies have been evaluated that the root extract of P. fulgens possesses antitumor [31], antioxidant [26], anthelmintic [25], and gastroprotective [24]. The root extract of P. fulgens in in vitro inhibit enzyme activities of amylase, α-glucosidase, β-glucosidase, and lipase in the liver, kidney, and eye lens of the diabetic mice [32].…”
Section: Discussionmentioning
confidence: 99%